What to expect from HER-2 directed therapies in advanced gastric cancer? - DANE, FAYSAL (MARMARA UNIV, FAC MEDICINE, 2015)
Gastric cancer is the second most common cause of cancer related death worldwide. Over 20% of the advanced gastric cancer are considered to be HER-2 positive. Studies investigating the prognosis of HER-2 positive advanced gastric cancer revealed conflicting results. Trastuzumab, a monoclonal antibody against HER-2, has shown a significant clinical activity in HER-2 positive gastric cancer patients. In this review, I will briefly summarize the clinical studies of anti-HER-2 therapies performed in HER-2 positive gastric carcinoma.
Keywords: Gastric cancer; HER-2/neu; Targeted therapy